Extending Graph Query Languages by Reduction - Weinell, Erhard (Electronic Communications of the EASST, 2008)
Graph grammars are a well-founded technology for visually specifying computations or the processing of complex data structures. Up to now, numerous languages and tools for graph transformations exist, whilst new ones are proposed regularly. However, these tools have no technical basis such as an execution framework or data storage in common. Instead, graph transformation machineries are usually implemented anew each time. The DRAGOS graph database is especially well-suited for building graph transformation systems, as it is able to store complex graph structures directly. Besides its storage functionality, the database also provides a Query & Transformation Mechanism which is able to handle complex queries upon the stored graphs, and to modify them accordingly. Being designed as a basis for graph and model transformation tools, this mechanism is required to allow a flexible adaptation and extension according to the respective applications’ needs. The present paper discusses how this requirement is covered by the proposed Query & Transformation Mechanism.